STRUKTUR DAN PERKEMBANGAN EMBRIO SOMATIK DARI KALUS KOTILEDON Eucalyptus pellita F. Muell. SECARA IN VITRO - THE STRUCTURE AND DEVELOPMENT OF SOMATIC EMBRYO FROM COTYLEDON CALLUS OF Eucalyptus pellita F. Muell. BY IN VIT - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABTRACT The structure and development of somatic embryos originated from cotyledon callus especially on red mahagony (Eucalyptus pellita F. Muell.) was studied using in vitro technique. The aim of this research was to study the effect explant source and concentrations of Picloram on potentially the embryogenic callus, the morphological and anatomical on embryogenic callus, and the stadiums of somatic embryo. The cotyledons of seedling age of 6, 8, and 10 days old was utilized as source of explant. This experiment consists of two parts: first, all the explant was cultured on MS medium + 0,25 mg 14 BA which was added with Picloram at 0